2021
DOI: 10.1021/acscatal.1c03099
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Calculations for Insight into the Heterocatalyst Reactivity and Mechanism in Persulfate-Based Advanced Oxidation Reactions

Abstract: Advanced oxidation processes (AOPs) based on persulfates such as peroxymonosulfate and peroxydisulfate via heterogeneous catalysts have been a research hotspot due to their outstanding performances in removing emerging organic contaminants (OCs). In this Review, we highlight the recent advances in theoretical simulations for persulfate-based AOPs (PS-AOPs) using density functional theory (DFT), with the emphasis on the catalyst properties and the mechanism of persulfate activation over a variety of heterogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 248 publications
(68 citation statements)
references
References 172 publications
1
59
0
Order By: Relevance
“…222 These factors are inherently determined by the surface chemistry of the catalysts, which could be tuned via introduction of heteroatoms and structural defects, and/or facet engineering. 227,228 For examples, the sp 2 -hybridized carbon materials featuring delocalized π network are more reactive for adsorption and electron conductivity than the sp 3hybridized and amorphous carbons. 227 Shao et al found that structural double-vacancies in multiwalled carbon nanotubes (MWCNTs) would induce charge polarization and decrease the HOMO−LUMO gap of MWCNTs, resulting in the intensification of PMS adsorption and the electron transfer from target pollutants to PMS.…”
Section: Selective Oxidation Achieved Bymentioning
confidence: 99%
See 1 more Smart Citation
“…222 These factors are inherently determined by the surface chemistry of the catalysts, which could be tuned via introduction of heteroatoms and structural defects, and/or facet engineering. 227,228 For examples, the sp 2 -hybridized carbon materials featuring delocalized π network are more reactive for adsorption and electron conductivity than the sp 3hybridized and amorphous carbons. 227 Shao et al found that structural double-vacancies in multiwalled carbon nanotubes (MWCNTs) would induce charge polarization and decrease the HOMO−LUMO gap of MWCNTs, resulting in the intensification of PMS adsorption and the electron transfer from target pollutants to PMS.…”
Section: Selective Oxidation Achieved Bymentioning
confidence: 99%
“…222 N doping could also change the charge distribution of the conjugated carbon network to benefit the interfacial electron transfer process. 228 nitrogenation, where the reduction of PDS occurred at the electron-rich pyridinic and pyrrolic N sites, whereas the oxidation of pollutants occurred at the electron-deficient atoms. 229 Generally, graphitic N is critical to initiate the electron transfer process, but different results available on this topic suggest further elucidation is still required.…”
Section: Selective Oxidation Achieved Bymentioning
confidence: 99%
“…State‐of‐the‐art in situ characterization techniques and theoretical calculations can be used as tools to reveal the potential reaction intermediates, structure‐performance relationship, and catalytic mechanism. [ 220 ] The photo‐Fenton reaction, especially for the system with in situ H 2 O 2 generation, involves complex reaction pathways with multiactivated species: O 2 •− can be produced from the one‐electron reduction of O 2 ; • OH can be generated from the activation of self‐produced H 2 O 2 ; photoexcited holes can be separated and transferred to the surface of catalyst for the direct oxidation of pollutants. Therefore, for in‐depth understanding of the reaction mechanism, it is essential to distinguish the specific roles of different activated species.…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%
“…The intrinsic and external characteristics of carbonaceous materials (Figure ), including dimensionality, pristine carbon configuration, crystallinity and defects, porosity, chemical active groups, and heterogeneous doping, affect the PS activation and thus the degradation of organic pollutants. It is noteworthy that the characteristics of the carbocatalyst mentioned above also determine the radical pathway, nonradical pathway, and adsorption and cleavage of pollutants …”
Section: Structural Diversities Of Carbonaceous Materials Complicate ...mentioning
confidence: 99%
“…It is noteworthy that the characteristics of the carbocatalyst mentioned above also determine the radical pathway, nonradical pathway, and adsorption and cleavage of pollutants. 13 2.1. Dimensionality.…”
Section: Structural Diversities Of Carbonaceous Materials Complicate ...mentioning
confidence: 99%